Tigers and butterflies - Han Suyin (London, 1990)
A collection of essays spanning 30 years on the culture, society and politics of a range of Third World countries, the most recent being a record of her meeting with the old Chinese leaders after Tiananmen Square. She addresses the important issues of our time - desertification, the continuing dominance of the North over the South, the rights of women, of immigrants and of indigenous minorities, birth control, the elimination of disease and the politics of aid. The author attacks the centres of power and privilege with irony, while always speaking for the men and women of the Third World in their struggle for justice and self determination. Her first literary success was "A Many Splendid Thing".
Keywords: Society